Strategy for Improving the Quality of Prime Service Through Wednesday Evening Services at the Jakarta Provincial Population Service - Ika Widiastuti (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2026)
The Jakarta Provincial Government's function in the Population Administration and Civil Registration service sector aims to increase public participation in population administration services, improve the performance of its apparatus, and enhance the quality of services provided by the Population and Civil Registration Office. However, the challenges faced by Jakarta residents in handling population administration matters at the Population and Civil Registration Office include high mobility and busy working hours, inadequate information and requirements, and the persistence of illegal levies. The purpose of this study was to analyze and describe the strategies implemented by the Jakarta Provincial Population and Civil Registration Office to improve service quality through the innovative Wednesday Evening Service program. The research method used was qualitative research. To improve service excellence, the Wednesday Evening Service was established at the Jakarta Provincial Population and Civil Registration Office. The results indicate that the Wednesday Evening Service has been running well, but there are constraints related to the internal budget of the Jakarta Service at the Population Administration Service Unit. The conclusion of this study is that there are stages carried out by Service at the Population Administration Service Unit Jakarta in implementing Wednesday Evening services as a strategy to improve the quality of prime services, namely including alternative action selection and resource allocation.